On The Notion of Historical Epistemology: A General Note - Atanasova, Veselina (Research Papers, 2024)
In historiography as methodology of writing history of the knowledge about economy, in recent years increasing attention has been focused on applying historical-epistemological approach (Stapleford, 2017; etc.). Among Bulgarian economists the significance of the field of epistemology in interpreting and analysis of economics discipline is outlined and discussed by Dobrinka Zlateva in Zlateva (2014; 2017; 2018). The topic of epistemology of economic knowledge is included in the curriculum for the students specializing in Political Economy at Political Economy department of the University of National and World Economy (UNWE), Sofia, Bulgaria. Generally, being subject to discussions in the world philosophy elite for decades, these questions remain rather unknown among economists and historians of economics, in the world as well with us. The present overview aims to draw the attention of the Bulgarian public interested in this direction to the developing specific field of the so called ‘historical epistemology’. A continuation of the present work will be another one revealing the meaning of historical epistemology for understanding economics and recent economics history.